Pengaruh Metode Pembelajaran Berbasis Masalah Terhadap Hasil Belajar pada Materi Keanekaragaman Hayati di Kelas X IPA SMAN 3 Sinjai (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The current study is a quasi-experimental study to determine the effect of the PBL model on student learning outcomes in the subject of biodiversity. The number of samples in this study were 162 students from class X which consisted of five classes. Class X3 as the experimental class and X4 as the control class with 33 students. Posttest results were then evaluated using descriptive statistical methods and inferential methods to produce the data collected. The results of the descriptive analysis showed a posttest score of 77.88 for the experimental class and 68.33 for the control class. In, inferential, analysis, statistics, prerequisites, tests, and hypotheses, tests are carried out. Based on the Prerequisite Test, it is known that the data is normally distributed and the population is homogeneous. It can be said that there is an effect of problem-based learning on learning outcomes on biodiversity material in class X, SMAN 3, and Sinjai.